2020
DOI: 10.2147/jep.s282669
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Anti-Diarrheal Activity of 80% Methanol Extracts of <em>Vernonia amygdalina</em> Delile (Asteraceae) Leaves in Mice</p>

Abstract: Introduction Diarrhea is a cause of morbidity and mortality, especially in children. Patients with diarrhea have been suffering from limited treatment options due to poor drug tolerance, side effect, and multi-drug resistance to almost all the current drug treatments. Therefore, it is important to search for a new therapeutic medicine that can effectively prevent the disease and safe. Vernonia amygdalina is an indigenous medicinal plant used traditionally for the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Thus, it is possible that the extract significantly inhibited gastrointestinal hypersecretion and enteropooling by increasing the reabsorption of electrolytes and water or by inhibiting the induced intestinal accumulation of fluid [ 53 ]. The anti-enteropooling activity of the extract may also be related to the presence of phytochemical constituents including flavonoids, steroids, and tannins [ [53] , [54] , [55] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible that the extract significantly inhibited gastrointestinal hypersecretion and enteropooling by increasing the reabsorption of electrolytes and water or by inhibiting the induced intestinal accumulation of fluid [ 53 ]. The anti-enteropooling activity of the extract may also be related to the presence of phytochemical constituents including flavonoids, steroids, and tannins [ [53] , [54] , [55] ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding showed that the extract could influence the peristaltic movement of the intestine, thereby indicating intestinal antimotility activity. Several plants have shown antidiarrheal activity by reducing gastrointestinal motility and secretion [ [50] , [51] , [52] , [53] , [54] , [55] ].…”
Section: Discussionmentioning
confidence: 99%
“…indica [ 28 ] and V . amygdalina [ 27 ], and the antiviral effects of M . indica against non-enteric viruses such as herpes simplex virus (HSV)-1 and -2 and HIV (reviewed in [ 51 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Some herbal medications reported in this study such as Agbo iba, 'Agbo jedi-jedi', Gangaria de flush and Goko herbal cleanser are mixtures of multiple herbs, while others are individual herbs (Table 3), some of which have been reported for antidiarrheal properties using castor oil-induced diarrhoea in Wistar rats [26][27][28][29][30][31][32][33][34]. In this report, we sought to investigate the impact of the unregulated use of herbal plants on AGE using in vitro assays to assess the antibacterial effects of ethanolic extracts of some of the reported plants.…”
Section: Antibacterial Efficacies Of Herbal Plantsmentioning
confidence: 95%
See 1 more Smart Citation